ChemInform Abstract: Efficient Synthesis of Sterically Hindered Arenes Bearing Acyclic Secondary Alkyl Groups by Suzuki—Miyaura Cross‐Couplings. Issue 31 (August 2015) - Li, Chengxi; Chen, Tianyu; Li, Bowen; Xiao, Guolan; Tang, Wenjun
Abstract A variety of di‐ortho‐substituted aryl bromides and some analogues is treated with acyclic secondary alkyl boronic acids in the presence of the efficient ligands (I).